ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR KOMIDITI NON MIGAS DI INDONESIA TAHUN 1985-2017 - Rauzatul Ulfa; Devi Andriyani (Jurnal Ekonomi Regional Unimal, 2019)
This study aims to analyze the Factors Affecting Non-Oil and Gas Commodity Exports in Indonesia in 1985-2017. The data used in this study are secondary data obtained from www.bps.go.id. The method used to analyze the relationship between the independent variables and the dependent variable is the multiple linear regression method. The results of the study partially showed that economic growth had a positive and significant effect on the exports of non-oil and gas commodities in Indonesia, the exchange rate and inflation did not affect the exports of non-oil and gas commodities in Indonesia. Simultaneously, the rate of economic growth and inflation had a positive and significant effect on non-oil and gas commodity exports in Indonesia.